2013
DOI: 10.1097/aln.0b013e31829102de
|View full text |Cite
|
Sign up to set email alerts
|

Protective Mechanical Ventilation during General Anesthesia for Open Abdominal Surgery Improves Postoperative Pulmonary Function

Abstract: Background: The impact of intraoperative ventilation on postoperative pulmonary complications is not defined. The authors aimed at determining the effectiveness of protective mechanical ventilation during open abdominal surgery on a modified Clinical Pulmonary Infection Score as primary outcome and postoperative pulmonary function. Methods: Prospective randomized, open-label, clinical trial performed in 56 patients scheduled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
171
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 399 publications
(195 citation statements)
references
References 48 publications
10
171
3
3
Order By: Relevance
“…The chest radiograph (X-rays) was used in all studies to detect atelectasis. Lung injury was diagnosed according to the American-European Consensus Conference definition in three studies,14 15 17 with no specific report in one study 16…”
Section: Resultsmentioning
confidence: 99%
“…The chest radiograph (X-rays) was used in all studies to detect atelectasis. Lung injury was diagnosed according to the American-European Consensus Conference definition in three studies,14 15 17 with no specific report in one study 16…”
Section: Resultsmentioning
confidence: 99%
“…An RCT in 40 patients having open abdominal surgery showed that compliance increased by 32% and airway resistance decreased by 21% for older patients undergoing open abdominal surgery with IOLPV compared with patients receiving conventional ventilation (P<0.001 and P=0.029, respectively) 88. A separate RCT found that patients receiving IOLPV performed better on spirometry than those receiving conventional ventilation as late as postoperative day 5 (mean forced expiratory volume in one second 1.63 (SD 0.55) v 1.23 (0.42) L/s, P<0.001; mean forced vital capacity 2.02 (0.52) v 1.57 (0.47) L/s, P<0.001) 89. More recently, several RCTs from the same group have found that IOLPV can decrease driving pressures for patients having abdominal surgery 7690…”
Section: Evidence Based Strategies For Perioperative Lung Protective mentioning
confidence: 98%
“…21 Obuhvaćeno je 56 bolesnika sa otvorenom abdominalnom hirurgijom u trajanju od najmanje 2 sata. CPI skor (Clinical Pulmonary Infection Score: skor koji služi za brzu dijagnostiku pneumonija udruženih sa mehaničkom ventilacijom -VAP) 22 bio je niži kod bolesnika sa protektivnom ventilacijom pluća. Bolesnici sa ovim oblikom ventilacije imali su bolju arterijsku oksigenaciju i manji broj radiografski detektovanih promena na plućima.…”
Section: Intraoperativna Protektivna Ventilacija I Rmunclassified